Haplotype-specific expression of exon 10 at the human MAPT locus. - Caffrey, T; Joachim, C; Paracchini, S; Esiri, M; Wade-Martins, R (2006)
Neurofibrillary tangles composed of exon 10+ microtubule associated protein tau (MAPT) deposits are the characteristic feature of the neurodegenerative diseases progressive supranuclear palsy (PSP) and corticobasal degeneration (CBD). PSP, CBD and more recently Alzheimer's disease and Parkinson's disease, are associated with the MAPT H1 haplotype, but the relationship between genotype and disease remains unclear. Here, we investigate the hypothesis that H1 expresses more exon 10+ MAPT mRNA compared to the other haplotype, H2, leading to a greater susceptibility to neurodegeneration in H1 carriers. We performed allele-specific gene expression on two H1/H2 heterozygous human neuronal cell lines, and 14 H1/H2 heterozygous control individual post-mortem brain tissue from two brain regions. In both tissue culture and post-mortem brain tissue, we show that the MAPT H1 haplotype expresses significantly more exon 10+ MAPT mRNA than H2. In post-mortem brain tissue, we show that the total level of MAPT expression from H1 and H2 is not significantly different, but that the H1 chromosome expresses up to 1.43-fold more exon 10+ MAPT mRNA than H2 in the globus pallidus, a brain region highly affected by tauopathy (maximum exon 10+ MAPT H1:H2 transcript ratio=1.425, SD=0.205, P<0.0001), and up to 1.29-fold more exon 10+ MAPT mRNA than H2 in the frontal cortex (maximum exon 10+ MAPT H1:H2 transcript ratio=1.291, SD=0.315, P=0.006). These data may explain the increased susceptibility of H1 carriers to neurodegeneration and suggest a potential mechanism between MAPT genetic variability and the pathogenesis of neurodegenerative disease.